TACE combined with portal particle implantation in a case of stage IIIa primary hepatocellular carcinoma treated with sequential anlotinib - Cheng Lin; Chen Chen; Guiliu Huang; Yueyong Li; Lifeng Zhao; Zhongheng Wei (Journal of Contemporary Brachytherapy, 2023)
Few cases of patients with Cheng’s type III portal vein tumor thrombus (PVTT) have been reported to achieve radical cure without recurrence over time. In this study, we reported on a 55-year-old male patient with a diagnosis of stage IIIa China liver cancer staging (CNLC), PVTT Cheng’s type III, mild cirrhosis, and chronic viral hepatitis B. TACE combined with radioactive iodine-125 ( 125 I) particle implantation was applied to achieve radical treatment with sequential oral anlotinib hydrochloride capsules. This case might serve as a reference for the treatment of this disease.